Impact of stimulation among non-crying neonates with intact cord versus clamped cord on birth outcomes: observation study - Shyam Sundar Budhathoki; Ashish KC; Nalini Singhal; Rejina Gurung; Srijana Sharma; Amit Bhandari; Susan Niermeyer; Leela Paudel; Jeevan Thapa; Omkar Basnet; Pratikshya Bhattarai; Ankit Acharya; et al. (BMJ Paediatrics Open)
Background Stimulation of non-crying neonates after birth can help transition to spontaneous breathing. In this study, we aim to assess the impact of intact versus clamped umbilical cord on spontaneous breathing after stimulation of non-crying neonates.Methods This is an observational study among non-crying neonates (n=3073) born in hospitals of Nepal. Non-crying neonates born vaginally at gestational age ≥34 weeks were observed for their response to stimulation with the cord intact or clamped. Obstetric characteristics of the neonates were analysed. Association of spontaneous breathing with cord management was assessed using logistic regression.Results Among non-crying neonates, 2563 received stimulation. Of these, a higher proportion of the neonates were breathing in the group with cord intact as compared with the group cord clamped (81.1% vs 68.9%, p<0.0001). The use of bag-and-mask ventilation was lower among those who were stimulated with the cord intact than those who were stimulated with cord clamped (18.0% vs 32.4%, p<0.0001). The proportion of neonates with Apgar Score ≤3 at 1 min was lower with the cord intact than with cord clamped (7.6% vs 11.5%, p=0.001). In multivariate analysis, neonates with intact cord had 84% increased odds of spontaneous breathing (adjusted OR, 1.84; 95% CI: 1.48 to 2.29) compared with those with cord clamped.Conclusions Stimulation of non-crying neonates with intact cord was associated with more spontaneous breathing than among infants who were stimulated with cord clamped. Intact cord stimulation may help establish spontaneous breathing in apnoeic neonates, but residual confounding variables may be contributing to the findings. This study provides evidence for further controlled research to evaluate the effect of initial steps of resuscitation with cord intact.